Studies on the effects of air curtain on heat and mass transfer in an enclosure - Poh, Hee Joo. (2008)
This project is on studying the heat and mass transfer in an enclosure due to an air curtain. There are three stages of study: Firstly, the commercial computational fluid dynamics (CFD) software, FLUENT Version 4.3 code was verified by numerical simulation on the airflow exiting from a nozzle and subsequently impinging on a flat plate in a pneumatic dimensional control system. Secondly, an experimental study on the effectiveness of air curtain in an air conditioned truck (1.64 m x 1.54 m x 2.84 m) with inside air temperature -11°C and outside ambient temperature 29°C was carried out. Lastly, an intensive computational study was carried out on hot and cold air interaction across the door for cases with and without air curtain in air-conditioned bus and truck, where there are significant temperature gradients existing between the inside environment of vehicles and the ambient environment.